The legal framework for biodiversity protection and conservation in South Africa: an appraisal of the listing of threatened species approach - Smith, Emma (Centre for Law and Society, 2026)
The conservation and protection of biodiversity is becoming increasingly relevant across all social, economic and environmental sections of the world we live in today. The world's conscience is in state of confusion as together with the need to ensure economic growth and development, there is also a need to preserve our natural environment for present and future generations to enjoy and benefit from. This crisis of environmental conscience can be dealt with in the laws that are made and in the implementation, management and enforcement of these laws. The Department of Environmental Affairs and Tourism (now known as the Department of Water and Environmental Affairs) in South Africa has promulgated a suite of conservation tools that may be used in order to ensure that species are protected inside and outside the borders of proclaimed conservation areas. One of these tools is to produce Threatened Species Lists (TSLs) that identify species that require protection from possible extinction due to predominantly human induced activities. Species are ·assigned categories of threat according to the degree to which they are under threat· and the nature of criteria that has been developed. This study focuses on the progression of TSLs from the development of global and national Red Data Lists to how they are incorporated into South African law as Lists of Critically Endangered, Endangered, Vulnerable and Protected Species published in terms of the National Environmental Management: Biodiversity Act 10 of 2004.